SPECIFICS OF ARTS THERAPISTS’ SELF-CARE STRATEGIES - Ozola, Aija; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Covid-19 pandemic poses significant increase in hazards to professionals’ health and well-being in the helping professions. Thus, their ability to provide compassionate and effective care to the population is at risk. Self-care is one of available resources that can strengthen mental health and promote psychological resilience in the face of the Covid-19 pandemic. The study aimed to explore arts therapists’ self-care strategies and their specifics compared with those of other psychological help providers and functional specialists. Based on Self-Care Strategies Questionnaire, a survey was conducted between March 2021 and January 2022. Following two instructions, respondents assessed 63 self-care activities by their importance and attainability. All items were rated on a 4-point Likert scale. The sample of 289 respondents comprised 73 arts therapists, 159 other psychological help providers and 57 other functional specialists. Although the assessment of arts therapists’ self-care strategies revealed a high degree of heterogeneity, in all of strategies importance was scored significantly higher compared with attainability. Six out of 14 self-care strategies and one separate activity revealed statistically significant differences between arts therapists’ and other functional specialists’ self-care strategies. There was no significant difference indicated between arts therapists’ and psychological help providers’ self-care strategies.